The Penguin Dictionary of Chemistry - Edited by Sharp, David W.A. (London Penguin Books, 2003)
The Penguin Dictionary of Chemistry is the reference book for students of all sciences, whatever their level, and for anyone who encounters chemical terms in the course of their work.nbsp; Comprehensive and packed with vital information, it has now been substantially updated to incorporate the very latest developments in this key subject area. Explains chemical terms from all branches of the subject Illustrated throughout.
Keywords: Chemistry -- Chimie -- Dictionnaires